Emotion recognition and social cognition in temporal lobe epilepsy and the effect of epilepsy surgery - Amlerova, Jana; Cavanna, Andrea E; Bradac, Ondrej; Javurkova, Alena; Raudenska, Jaroslava; Marusic, Petr (Epilepsy & behavior, 2014)
The abilities to identify facial expression from another person's face and to attribute mental states to others refer to preserved function of the temporal lobes. In the present study, we set out to evaluate emotion recognition and social cognition in presurgical and postsurgical patients with unilateral refractory temporal lobe epilepsy (TLE). The aim of our study was to investigate the effects of TLE surgery and to identify the main risk factors for impairment in these functions. We recruited 30 patients with TLE for longitudinal data analysis (14 with right-sided and 16 with left-sided TLE) and 74 patients for cross-sectional data analysis (37 with right-sided and 37 with left-sided TLE) plus 20 healthy controls. Besides standard neuropsychological assessment, we administered an analog of the Ekman and Friesen test and the Faux Pas Test to assess emotion recognition and social cognition, respectively. Both emotion recognition and social cognition were impaired in the group of patients with TLE, irrespective of the focus side, compared with healthy controls. The performance in both tests was strongly dependent on the intelligence level. Beyond intelligence level, earlier age at epilepsy onset, longer disease duration, and history of early childhood brain injury predicted social cognition problems in patients with TLE. Epilepsy surgery within the temporal lobe seems to have neutral effect on patients' performances in both domains. However, there are a few individual patients who appear to be at risk of postoperative decline, even when seizure freedom is achieved following epilepsy surgery.
Keywords: Seizures; audiovizuální záznam; neuropsychologické testy; Humans; Longitudinal Studies; Video Recording; Temporal lobe epilepsy; Recognition, Psychology; lidé středního věku; kognice; epilepsie temporálního laloku; Neurosurgical Procedures; Emotions; Female; mladý dospělý; dospělí; výsledek terapie; lidé; elektroencefalografie; Adult; Epilepsy surgery; Neuropsychological Tests; ženské pohlaví; longitudinální studie; Male; Middle Aged; Retrospective Studies; emoce; Treatment Outcome; Epilepsy, Temporal Lobe; rozpoznávání (psychologie); Cross-Sectional Studies; Young Adult; Electroencephalography; průřezové studie; retrospektivní studie; Emotion recognition; mužské pohlaví; Cognition; Social cognition; neurochirurgické výkony